Rancang Bangun Inverter sebagai Driver Motor Induksi 3 Fasa - Susi Susanti; Dadang Lukman Hakim; Yoyo Somantri (ELECTRANS, 2016)
In the last 10 years the development of energy conversion technology has been developing very fast. This is due to the continuous penetration in power electronics to power plants. Estimated more than 85% from every single type of motor which used in industries and domestic applications, induction motor is the most selected choice. The majority of drive in industries are using AC induction motor because of its robust, reliable, and relatively cheap. Induction motor mainly used in constant speed application because voltage supply for frequency variable was not available. The designed inverter circuit in this research was used as a three phase induction motor driver which needs voltage supply of 380 Volts. Besides, the designed inverter was expected to handle a continuous load of 1000 VA. In the design process and the research which conducted consists of simulation stage and building the prototype of inverter circuit as a three phase induction motor driver. At the design and the research that conducted in this paper are consisted of three components, which are sinusoidal PWM circuit, inverter circuit, and low pass passive filter circuit. To reduce the harmonics in the waveform of inverter’s output, then used sinusoidal PWM switching scheme. Therefore the purpose of this research is to know how to design an inverter, the specification of inverter design, and the switching scheme that is used in the inverter. The reason for conducting this research is to pursue the needs of inverter utilities in the industries. The research method that is used in this research is a qualitative method which the inverter design data is compared with the tested prototype.